ENHANCING WORK AND EMPLOYMENT OPPORTUNITIES FOR PERSONS WITH DISABILITIES (PWDs) - Manzoor, Rameez; RM, Channaveer (International Journal of Psychosocial Rehabilitation, 2020)
Worldwide, it has been estimated that 15% of the total population have developed one or other type of disability. Among these persons with disabilities (PWDs), 80% belong to the working-age group. Mostly, PWD’s are being denied to get involved in decent work and employment opportunities. They face attitudinal, physical and communication barriers during their daily life, especially at work. They lack social protection and live in extreme poverty as disability and poverty is a vicious cycle. It is evident that in low and middle-income countries, working-age persons having a disability are less employed than persons without disabilities. Less involvement in the labour market is the leading factor towards poverty of PWD’s. To address these issues, different countries have formulated laws that prohibit discrimination based on a person’s disability. Implementing such laws helps in the empowerment of persons with disabilities. Rehabilitative services in terms of vocational training, employment opportunities, skill development and self-employment for PWD’s helps in their inclusion in society and restoring their capacities to get decent work and employment.